Autonomous Actions that Emerge from Strategizing in the Preservation of Culture and Tradition of a Collective of Artisanal Fishers in Florianópolis – SC - Rocha, Robson Vander Canarin da; Perito, Barbara Zandomenico; Lavarda, Rosalia Aldraci Barbosa (Organizações & Sociedade, 2022)
Autonomous actions can be considered emerging actions related to strategic actions and have the potential to influence the organization’s strategy, and strategizing is strategy happening in practice. This study aimed to understand how autonomous actions emerge from strategizing in alternative organizational contexts. Qualitative research was carried out through a case study in a collective of artisanal mullet fishers in Campeche (Florianópolis – SC). Data collection took place through interviews, non-participant observation, and documents. Data analysis was performed using the Pattern Matching technique to compare theoretical-empirical patterns. The results indicate that the autonomous actions that emerge from strategizing, in the context studied, are desired and incorporated by the organization when they help to reinforce its strategic practices to preserve the culture and tradition of artisanal fishing. Our research found autonomous actions and emerging strategic actions imbricated in cultural and traditional principles and values in a shared way, connected with organizational strategy, in an effort of resistance to preserve their primitive forms of organization, structure, and artisanal production. Depending on the context and prevailing rationality, autonomous actions can connect directly with the principles and values shared in everyday practices, from the micro-organizational level, reinforcing and strengthening the strategy, regardless of the financial return.